Mosques and Literacy Reading of the Quran: Empowering Mosques as Educational Centers during Covid-19 Outbreak - Syalawaty, Diyan; Aldi, Ahmad; Tanti, Tanti; Utami, Wiji; Deliza, Deliza (Institut Agama Islam Negeri Sorong, 2021)
There are differences in the mosques performed before and during the Covid-19 pandemic, but these differences do not hinder the mosque's goals. This study aims to find out how the role of mosques in fostering reading the Qur'an during the Covid-19 pandemic and the inhibiting and supporting factors. Research on the involvement of mosques in the development of reading the Koran during the pandemic has been explored using a qualitative case study approach. The data collected was obtained using field research methods and literature studies. The findings in this study explain that the power of mosques as educational centers continues during the Covid-19 pandemic. The spirit of reading the Koran during the pandemic encountered several obstacles. This study provides distribution in theory and practice for Muslims during the Covid-19 pandemic for empowering mosques as an educational center.